Prevalence and diagnostic accuracy of different diagnostic tests for Chagas disease in an indigenous community of the Paraguayan Chaco. - Sofia Ardiles-Ruesjas; Vidalia Lesmo; Valeria González-Romero; Zully Cubilla; Lilian Chena; Claudia Huber; María José Rivas; Patricia Saldaña; Adrián Carrascosa; Susana Méndez; Sergi Sanz; Sören L Becker; et al. (PLoS Neglected Tropical Diseases)
Introduction Chagas disease (CD), caused by the protozoan Trypanosoma cruzi (T. cruzi), poses a major health challenge in Paraguay, especially in the resource-limited Chaco region. Rapid diagnostic tests (RDTs) are valuable tools to enhance diagnostic access. This study evaluates CD prevalence and risk factors in an indigenous community in the Paraguayan Chaco and validates the national RDT-based diagnostic algorithm for resource-limited settings against the recommended standard algorithm, which relies solely on conventional serological tests. Methodology A descriptive cross-sectional study was conducted in Casanillo, Presidente Hayes, Paraguay. In July 2023, a two-week field campaign was executed using a non-probability convenience sampling method targeting individuals aged over 9 months. Screening involved a single RDT, with positives confirmed via enzyme-linked immunosorbent assay (ELISA). Algorithm accuracy was validated externally at the National Reference Laboratory of Paraguay against the standard algorithm, which, in this study, included an ELISA and Hemagglutination test. Discordant cases were resolved with a second ELISA or Immunofluorescence. Results The study involved 999 participants, with a median age of 26 years (IQR 12-45), and 51.1% were female. The RDT-based diagnostic algorithm showed 97.1% agreement (κ = 0.94, 95%CI: 0.90-0.98) with the standard algorithm. The RDT alone had 96.0% agreement (κ = 0.91, 95%CI: 0.87-0.96), while the confirmatory ELISA had 94.3% agreement (κ = 0.88, 95%CI: 0.83-0.93). The algorithm's sensitivity/specificity (95%CI) were 94.6% (89.2-97.8)/98.6% (96.1-99.7), with the RDT at 94.6% (89.2-97.8)/96.8% (93.6-98.7) and the ELISA at 96.9% (92.3-99.2)/92.7% (88.5-95.8). T.cruzi infection seroprevalence was 12.6% (95%CI: 9.56-16.52). Age, Sanapaná ethnicity, and awareness of CD vectors were significantly associated with infection odds. No significant associations were found with other typical CD risk factors, clinical history, or health habits. Conclusion The study underscores the high burden of T. cruzi infection in indigenous communities in the Paraguayan Chaco, urging immediate interventions for improved diagnosis and treatment. The combination of RDTs with conventional serology for diagnostic screening in resource-constrained settings proved useful, and its further use is encouraged.